對生命倫理學相關問題的思考: Thoughts on Several Bioethical Issues - CHEN, Xiaoyang; WANG, Wenfei; JI, Haoyi (International Journal of Chinese & Comparative Philosophy of Medicine, 2014)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. The cultural authority of bioethics has recently been subject to fierce debate. Although there appear to be no specific reasons for this deep divergence, it is necessary to clarify the problems and attempt to resolve the crisis. In this article, we discuss some ofthe points made by Professor Solomon in his recent paper. Bioethics has been culturally and socially rooted throughout its development since the 1960s. It can even be regarded as a kind of cultural product, shaped by diverse national cultures, religions, political systems and so on. However, it is impossible to deny that bioethics today faces challenges arising from multiculturalism and universality. It is important to respect cultural differences while at the same time helping to make global cognition possible. Bioethics scholars must work together to develop the discipline further. We strongly recommend that a balance is kept during this process to ensure a harmonious academic atmosphere. DOWNLOAD HISTORY | This article has been downloaded 50 times in Digital Commons before migrating into this platform.